Manajemen Pendidikan Karakter Berbasis Tradisi Pesantren di SMP Islam Al-Kahfi Somalangu Kebumen - Siti Atikah; Imam Satibi; Muna Fauziah (LPPM Institut Agama Islam Nahdlatul Ulama Kebumen, 2021)
The purpose of this study is to analyze the management of character education based on the tradition of pesantren at SMP Islam Al-Kahfi Somalangu Kebumen. Qualitative research is used in this study. The research location is in Al-Kahfi Islamic Middle School Somalangu Kebumen. Data was collected through observation, interviews, and documentation. The respondents were principals, vice principals, counseling guidance teachers, classroom teachers, and students. The data were analyzed through the stages of data collection, data reduction, data presentation, and drawing conclusions. The findings show that the management of character education based on the tradition of pesantren at SMP Islam al-Kahfi is by planning, organizing, implementing, and controlling/evaluating, while character education based on pesantren is carried out through learning, extracurricular, and habituation to students with identical religious characters, honest, tolerant, disciplined, love the homeland, friendly and care for the environment.